Study of the conditions for determining some chloromethoxybenzoic acid derivatives - Maga, Ivan; Kushniruk, Anna; Rujinskiy, Mykhailo; Avramenko, Olga (Problems of Environmental Biotechnology, 2021)
Chloromethoxybenzoic acid (CBA) Derivatives are active ingredients, are an integral part of many pesticides, important among which 3-chlorine-5-methoxybenzoic acid have, which is used as isopropylamine salts, as well as 2-chloro-4-methoxybenzoic acid used in the form of butylocutyl esther as herbicidal preparations. The residual amounts of these and other pesticides have a detrimental effect on the environment. An important role in the detoxification of pesticides have the soil microorganisms, but, unfortunately, the CBA derivatives are a recalcitrant substrate and are poorly decomposed by these microorganisms, since the CBA prevents the proliferation of such microorganisms. Therefore, the control of residues of CBA derivatives in environmental objects is important, as well as the development of new highly sensitive methods for determining CBA derivatives in such objects. To determine derivatives, CBA is most often used the Revers Phases HPLC method.